Adoption of Digital Technology in Money Transactions: A Sociological Analysis of Rural Areas in Chhattisgarh - Dr. Falendra Kumar; Prof. L. S. Gajpal (International Journal of Scientific Research in Humanities and Social Sciences, 2026)
Digital technology has emerged as a transformative force in contemporary financial systems, redefining the modes of monetary exchange and economic interaction. In India, digital payment mechanisms are promoted as tools for efficiency, transparency, and inclusive growth. However, their acceptance in rural society remains uneven and socially conditioned. The present study explores rural respondents’ perceptions regarding the use of technology for money transactions, the types of digital payment applications preferred, and the extent to which online payments are adopted in everyday economic activities. The study is based on primary data collected from 248 respondents across four districts of Chhattisgarh—Raipur, Rajnandgaon, Janjgir-Champa, and Dantewada. The findings reveal that despite increasing exposure to digital platforms, a majority of rural respondents continue to rely on traditional cash-based transactions. Factors such as limited digital literacy, infrastructural inadequacies, and security concerns significantly influence technology adoption. The study emphasizes that digital payment systems, while technologically efficient, require strong social acceptance and institutional support to achieve meaningful financial inclusion in rural society.